Fennema's food chemistry - Damodaran, Srinivasan (CRC Press/Taylor & Francis, 2008)
Substantially updated to reflect current research and containing a new chapter on the impact of biotechnology on food supply and quality, this is the first edition to honor the original editor by including his name in the title. This edition continues in the tradition of identifying bioactive agents and their role inhuman health and examining major food components (water and ice, carbohydrates, lips, amino acids, peptides, proteins and enzymes) and minor food components (vitamins, minerals, colorants, flavors, additives, bioactive substances, nutraceuticals, toxicants). It also covers food systems including dispersed systems, chemical and physical interactions of components in food systems, characteristics of milk. Physiology and chemistry of edible muscle tissues, and post-harvest physiology of edible plant tissues). This serves both as a classroom text and a professional reference. Annotation